A diferença como política de resistência e de ressignificação da subjetividade feminina em campos de saberes masculinos - Neiva Furlin; Marlene Tamanini (Ciências Sociais Unisinos)
This article analyzes narratives of women teachers inserted into the context of teaching Catholicism in a traditionally masculine space structured to be unintelligible to women. The aim is to show how these teachers, who work in the field of theological knowledge, are formed and assert themselves positively as feminine subjects. The study is qualitative, based on the hermeneutic interpretation of the narratives of fourteen teachers, inserted into three Catholic institutions located in the South and Southeast regions of Brazil. In order to analyze how women theologians become subjects in their positions and policy strategies, we adopt theoretical presuppositions of feminism, gender studies and, especially, the notion of sexual difference of Rosi Braidotti, as one of the epistemological fields of feminist theory. The study shows that the teachers deessentialize the content of difference from its situated action as a political strategy in the production of an ethics of the self. This situation indicates that the redefinition of sexual difference and gender subjectivity, in this context, functions positively, even if it remains marked by a symbolic, hierarchical, celibate and masculine structure in which difference frequently continues being driven, in a negatively meaningful way by the aforementioned essentializations, to lower levels of competence regarding women.